Proceedings of the 1st International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2009
DOI: 10.1145/1620509.1620512
|View full text |Cite
|
Sign up to set email alerts
|

Assessing subjective response to haptic feedback in automotive touchscreens

Abstract: The increasing use of touchscreen interfaces in vehicles poses challenges to designers in terms of optimizing safety, usability and affective response. It is thought that the application of haptic feedback to the touchscreen interface will help to improve the user experience in all of these areas. This paper describes the initial outcomes of a study to investigate user responses to haptic touchscreens using a simulated driving scenario based on the Lane Change Test, along with representative use case tasks. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…This paper reports on and extends the findings of a 2009 study conducted to evaluate the effects of different combinations of touchscreen visual, audible, and haptic feedback on driving and task performance, affective response, and subjective workload; the initial findings of which were originally published in (M. J. Pitts et al, 2009). A total of 48 non-expert users completed the study.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…This paper reports on and extends the findings of a 2009 study conducted to evaluate the effects of different combinations of touchscreen visual, audible, and haptic feedback on driving and task performance, affective response, and subjective workload; the initial findings of which were originally published in (M. J. Pitts et al, 2009). A total of 48 non-expert users completed the study.…”
mentioning
confidence: 78%
“…This paper reports on the findings of a study into the effects of multimodal touchscreen feedback in an automotive context, conducted in 2009 and originally reported in [8]. The initial findings from the earlier publication are extended with a revised analysis of the subjective data and the addition of objective measures of task performance and driving behaviour, along with discussion of contemporary studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, related work has reported the benefits of providing haptic feedback with in-car controls (e.g. [5,7,16,17,19,21]). We wanted to see if haptic feedback would still be effective for input in real world driving situations.…”
Section: Haptic Feedbackmentioning
confidence: 99%
“…analog, digital and virtual speedometers) found in cars and safety concerns regarding driver distraction due to complex interactions with in-car systems. Therefore, studies such as Pitts et al [17] explored the effectiveness of haptic feedback for in-car touchscreens and found that a combination of visual, audible and haptic feedback was subjectively preferred over visual feedback only. Richter et al [19] showed that haptic feedback reduced input error rate and improved overall task completion time on a forcesensitive touchscreen device in their simulated driving study.…”
Section: Introductionmentioning
confidence: 99%
“…[7,12,22,23,25,27]) has found that touch input with in-car interfaces improved with the addition of haptic feedback, so we tested the input techniques with vibrotactile cues to see if it influenced targeting performance.…”
Section: Scrolling Taskmentioning
confidence: 99%